SRGN-Triggered Aggressive and Immunosuppressive Phenotype in a Subset of TTF-1–Negative Lung Adenocarcinomas. (15th September 2021) - Tanaka, Ichidai; Dayde, Delphine; Tai, Mei Chee; Mori, Haruki; Solis, Luisa M; Tripathi, Satyendra C; Fahrmann, Johannes F; Unver, Nese; Parhy, Gargy; Jain, Rekha; Parra, Edwin R; Murakami, Yoshiko; et al.
Abstract: Background: Approximately 20% of lung adenocarcinoma (LUAD) is negative for the lineage-specific oncogene Thyroid transcription factor 1 ( TTF-1 ) and exhibits worse clinical outcome with a low frequency of actionable genomic alterations. To identify molecular features associated with TTF-1–negative LUAD, we compared the transcriptomic and proteomic profiles of LUAD cell lines. SRGN, a chondroitin sulfate proteoglycan Serglycin, was identified as a markedly overexpressed gene in TTF-1–negative LUAD. We therefore investigated the roles and regulation of SRGN in TTF-1–negative LUAD. Methods: Proteomic and metabolomic analyses of 41 LUAD cell lines were done using mass spectrometry. The function of SRGN was investigated in 3 TTF-1–negative and 4 TTF-1–positive LUAD cell lines and in a syngeneic mouse model (n = 5 to 8 mice per group). Expression of SRGN was evaluated in 94 and 105 surgically resected LUAD tumor specimens using immunohistochemistry. All statistical tests were 2-sided. Results: SRGN was markedly overexpressed at mRNA and protein levels in TTF-1–negative LUAD cell lines ( P < .001 for both mRNA and protein levels). Expression of SRGN in LUAD tumor tissue was associated with poor outcome (hazard ratio = 4.22, 95% confidence interval = 1.12 to 15.86, likelihood ratio test, P = .03), and with higher expression of Programmed cell death 1 ligand 1 (PD-L1) in tumor cells and higher infiltration of Programmed cell death protein 1–positive lymphocytes. SRGN regulated expression of PD-L1 as well as proinflammatory cytokines, including Interleukin-6, Interleukin-8, and C-X-C motif chemokine 1 in LUAD cell lines; increased migratory and invasive properties of LUAD cells and fibroblasts; and enhanced angiogenesis. SRGN was induced by DNA demethylation resulting from Nicotinamide N-methyltransferase–mediated impairment of methionine metabolism. Conclusions: Our findings suggest that SRGN plays a pivotal role in tumor–stromal interaction and reprogramming into an aggressive and immunosuppressive tumor microenvironment in TTF-1–negative LUAD.